Development of PAI Teacher Professionalism through Reflective and Collaborative Learning - Hariyati; Afifulloh, Mohammad; Fahmi Hidayatullah, Muhammad (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze and formulate the Islamic Reflective-Collaborative Model (RKI) as a concept for developing the professionalism of Islamic Religious Education (PAI) teachers in Klojen District, Malang City. This model stems from the low practice of reflection and peer collaboration in facing the demands of the Merdeka Curriculum and the digital era. The research employs a qualitative descriptive approach with phenomenological methods to explore the meaning of teachers' experiences in developing their professional competencies. Data were collected through in-depth interviews, participatory observation, and documentation, with participants including junior and senior high school PAI teachers, principals, and PAI supervisors. Data analysis used the Miles & Huberman interactive model, with validation through source and technique triangulation. The research findings reveal four main discoveries: self-reflection, peer reflection, interdisciplinary collaboration based on Islamic values, and spirituality internalization. The resulting RKI Model is conceptual in nature, emphasizing the integration of reflection, collaboration, and religious values as the foundation for PAI teacher professional development. This research has implications for strengthening theory, participatory training policies, and the formation of reflective communities in Islamic educational environments